2023
DOI: 10.3389/fspor.2023.1130131
|View full text |Cite
|
Sign up to set email alerts
|

(Re)conceptualizing movement behavior in sport as a problem-solving activity

Abstract: The use of the term problem-solving in relation to movement behavior is an often-broached topic within kinesiology. Here we present a clear rationale for the concept of problem-solving, specifically pertaining to the skilled organization of movement behaviors in sport performance, and the respective processes that underpin it, conceptualized within an ecological dynamics framework. The movement behavior that emerges in sport can be viewed as a problem-solving activity for the athlete, where integrated movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…In the simulator Frontiers in Sports and Active Living 07 frontiersin.org movement solutions (22) for such alive movement problems encountered during a race. Therefore, on-track practice sessions should prioritize tasks related to turn-ability, particularly focusing on experimentation to identify the optimal racing line.…”
Section: Goal Specific Examplesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the simulator Frontiers in Sports and Active Living 07 frontiersin.org movement solutions (22) for such alive movement problems encountered during a race. Therefore, on-track practice sessions should prioritize tasks related to turn-ability, particularly focusing on experimentation to identify the optimal racing line.…”
Section: Goal Specific Examplesmentioning
confidence: 99%
“…The drivers' ability to perform these turns successfully can be seen as a problem-solving activity ( 22 ). Indeed, Myszka et al ( 22 ) suggested that athletes face continually changing information.…”
Section: Training For Turn-abilitymentioning
confidence: 99%
See 3 more Smart Citations